Differential Sensitization of Different Prostate Cancer Cells to Apoptosis - Guo, Jinjin (SAGE Publications, 2010)
Although protein kinase C (PKC) plays an important role in sensitizing prostate cancer cells to apoptosis, and suppression of PKC is able to trigger an apoptotic crisis in cells harboring oncogenic ras, little is known about whether dyregulation of Ras effectors in prostate cancer cells, together with loss of PKC, is synthetically lethal. The current study aims at investigating whether prostate cancer cells with aberrant Ras effector signaling are sensitive to treatment with HMG (a PKC inhibitor) for the induction of apoptosis. We show that prostate cancer DU145 cells expressing a high level of JNK1 become susceptible to apoptosis after treatment with HMG, in which caspase 8 is activated and cytochrome c is released to the cytosol. In contrast, the addition of HMG sensitizes LNCaP or PC3 prostate cancer cells harboring an active Akt to apoptosis, in which ROS is upregulated to induce the UPR and GADD153 expression. The concurrent activation of JNK1 and Akt has an additive effect on apoptosis following PKC suppression. Thus, the data identify Akt and JNK1 as potential targets in prostate cancer cells for PKC inhibition–induced apoptosis.